2004
DOI: 10.1096/fj.03-0792fje
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of nitric oxide synthases (NOS 1‐3) in human skeletal muscle following exercise countermeasure during 12 weeks of bed rest

Abstract: Adaptive changes of major body systems in astronauts during spaceflight can be simulated by strict anti-orthostatic head-down tilt (HDT) bed rest (BR), a ground-based microgravity (microG) model that provides a meaningful opportunity to study atrophy mechanisms and possible countermeasures under controlled experimental conditions. As nitric oxide (NO) signaling is linked to muscle activity, we investigated altered expression of the three major isoforms of nitric oxide synthase (NOS 1-3) at cellular compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
103
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(124 citation statements)
references
References 87 publications
20
103
1
Order By: Relevance
“…The downregulated constitutive NO synthase (NOS) could be responsible for lowered nitric oxide production and may disrupt nitric oxide signaling in skeletal muscle arterioles, thus impairing vasodilatation in old age (45). Also, in a study of atrophy induction by horizontal bed rest in young males, it was observed that sarcolemmal NOS1 immunofluorescence in the vastus lateralis muscle increased (52). These opposite effects may be explained by age-related variations in muscle conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulated constitutive NO synthase (NOS) could be responsible for lowered nitric oxide production and may disrupt nitric oxide signaling in skeletal muscle arterioles, thus impairing vasodilatation in old age (45). Also, in a study of atrophy induction by horizontal bed rest in young males, it was observed that sarcolemmal NOS1 immunofluorescence in the vastus lateralis muscle increased (52). These opposite effects may be explained by age-related variations in muscle conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Human subjects confined to bed for 90 days were found to experience atrophy of the vastus lateralis (thigh) and soleus (calf) muscles. This atrophy was accompanied by reduced nNOSμ expression and sarcolemmal localization in the vastus lateralis only, suggesting that atrophic regulation of nNOSμ occurs by unidentified muscle-specific mechanisms (Rudnick et al 2004). Thigh muscle size and nNOSμ localization are preserved if bed rest is accompanied by ergometer exercise, which also increases nNOSμ expression above pre-bed rest levels.…”
Section: Inactivity-dependent Regulation Of Nnos Expression and Catalmentioning
confidence: 95%
“…Most human studies suggest that endurance-type exercise leads to increased nNOSμ expression (Frandsen et al 2000;Rudnick et al 2004;McConell et al 2007). For example, endurance-trained athletes have significantly higher (approx.…”
Section: Nnos and Skeletal Muscle Adaptation To Exercisementioning
confidence: 99%
“…NO is synthesised enzymatically by three recognised NO synthase (NOS) isoforms termed; neuronal NOS (nNOS), endothelial NOS (eNOS) and inducible NOS (iNOS), with nNOS being the primary isoform in the skeletal muscle (Frandsen et al, 1996;Rudnick et al, 2004). nNOS and eNOS are primarily localised in the sarcolemma and vascular endothelium, respectively (Frandsen et al, 1996), although both isoforms also exist in the mitochondria (Frandsen et al, 1996;Kobzik et al, 1994).…”
Section: Nitric Oxidementioning
confidence: 99%